P03 Baseline characteristics and early mental health sequelae in adolescents presenting after sexual assault. (27th April 2015) - Clarke, V; Armitage, AJ; Kramer, T; Wellings, K; Goddard, A; Welch, JM; Viner, RM; Khadr, SN
Abstract : Background: Estimates suggest 29% of rapes and 41% of sexual assaults reported to the police involve victims <17 years. Longitudinal research evaluating outcomes following adolescent sexual assault is lacking. Aims: To describe the characteristics of adolescent sexual assault and early mental health sequelae in young people (YP) presenting to the sexual assault referral centres (SARCs) serving a large UK city. Methods: Design : Prospective longitudinal cohort study. Study population : We approached all YP aged 13–17 years presenting to a SARC within six weeks of assault. Baseline data collection included psychological evaluation using the Short Moods and Feelings Questionnaire (depressive symptoms), Self-Report for Childhood Anxiety-Related Disorders (SCARED)-short form (anxiety symptoms) and Impact of Events Scale (post-traumatic symptoms). Results: 30% of YP consented to take part. Data are available for the first 94 participants (mean [SD] age: 15.16 [1.24] years; 96% female). Those with learning disability and young people of black ethnicity were over-represented compared to the local population (18% vs. 2.5%, and 23% vs . 11%, respectively). 15% had a history of previous non-consensual sex and 44% were known to social services. 39% had sought help for mental health difficulties in the previous year and 37% had previously self-harmed. Participants experienced vaginal rape in 72% of cases, oral rape in 40% and anal rape in 13%. 44% of assaults involved physical violence and 9% involved a weapon. 29% involved alcohol and 14% involved drugs. 36% were stranger assaults, 47% involved an acquaintance and the remainder involved partners or ex-partners (3%), or a relative (5%). Assailants were most commonly aged 15–20 (41%) or 21–30 (22%), with 12% <15 years. Early psychological outcomes: 73% had significant depressive symptoms, 90% had a high likelihood of post-traumatic stress disorder, 69% met criteria for panic disorder or significant somatic symptoms, and 60% met criteria for generalised anxiety disorder. Conclusions: Adolescents accessing SARCs are a vulnerable population and exhibit high levels of psychological morbidity within six weeks of sexual assault. Longitudinal research is critically important for evaluating outcomes over time and to inform interventions and preventive programmes.